2008
DOI: 10.1104/pp.108.126003
|View full text |Cite
|
Sign up to set email alerts
|

A Stress-Inducible Resveratrol O-Methyltransferase Involved in the Biosynthesis of Pterostilbene in Grapevine

Abstract: Stilbenes are considered the most important phytoalexin group in grapevine (Vitis vinifera) and they are known to contribute to the protection against various pathogens. The main stilbenes in grapevine are resveratrol and its derivatives and, among these, pterostilbene has recently attracted much attention due both to its antifungal and pharmacological properties. Indeed, pterostilbene is 5 to 10 times more fungitoxic than resveratrol in vitro and recent studies have shown that pterostilbene exhibits anticance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
145
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(159 citation statements)
references
References 54 publications
13
145
1
Order By: Relevance
“…Similar results were observed in MYB15 overexpressing hairy roots ( Figure 5B; see Supplemental Figure 6 online). It has been demonstrated that stilbenes, and in particular d-viniferin, an oxidative resveratrol dimer, and pterostilbene, the 3,5-dimethoxy analog of resveratrol, have fungitoxic properties (Pezet et al, 2003(Pezet et al, , 2004Schmidlin et al, 2008) and that the glycosylation of stilbenes may occur in plant cells both to protect cells from their potential toxic effects and to protect resveratrol from degradation Hipskind and Paiva, 2000). This might explain the high amount of trans-piceid in the MYB15 transgenic hairy roots in comparison with the relatively low amounts of other modified stilbenes (see Supplemental Figure 6 online).…”
Section: Ectopic Expression Of Myb15 In Grapevine Hairy Roots Resultsmentioning
confidence: 99%
“…Similar results were observed in MYB15 overexpressing hairy roots ( Figure 5B; see Supplemental Figure 6 online). It has been demonstrated that stilbenes, and in particular d-viniferin, an oxidative resveratrol dimer, and pterostilbene, the 3,5-dimethoxy analog of resveratrol, have fungitoxic properties (Pezet et al, 2003(Pezet et al, , 2004Schmidlin et al, 2008) and that the glycosylation of stilbenes may occur in plant cells both to protect cells from their potential toxic effects and to protect resveratrol from degradation Hipskind and Paiva, 2000). This might explain the high amount of trans-piceid in the MYB15 transgenic hairy roots in comparison with the relatively low amounts of other modified stilbenes (see Supplemental Figure 6 online).…”
Section: Ectopic Expression Of Myb15 In Grapevine Hairy Roots Resultsmentioning
confidence: 99%
“…Then, Katsuyama et al (2007) confirmed O-methylating activity of PMT towards stilbenes in vitro using a homologous gene from Oryza sativa and expressing it in E. coli. The grapevine and sorghum resveratrol O-methyltransferases (ROMT or OMT) have been shown to catalyze the formation of dimethylated resveratrol derivative, pterostilbene, both in vitro and in planta (Schmidlin et al 2008;Rimando et al 2012). Transcription of the PMT and ROMT genes was induced in needles of Scots pine and in grapevine leaves, respectively, in response to biotic and abiotic stresses, such as fungal infection, UV irradiation, ozone, wounding, or heavy metal treatment (Chiron et al 2000a;Schmidlin et al 2008).…”
Section: Stilbene Biosynthesismentioning
confidence: 99%
“…The grapevine and sorghum resveratrol O-methyltransferases (ROMT or OMT) have been shown to catalyze the formation of dimethylated resveratrol derivative, pterostilbene, both in vitro and in planta (Schmidlin et al 2008;Rimando et al 2012). Transcription of the PMT and ROMT genes was induced in needles of Scots pine and in grapevine leaves, respectively, in response to biotic and abiotic stresses, such as fungal infection, UV irradiation, ozone, wounding, or heavy metal treatment (Chiron et al 2000a;Schmidlin et al 2008). A recent study identified for the first time the stilbenoid-specific prenyltransferase involved in the biosynthesis of prenylated stilbenes using peanut hairy root cultures producing arachidins .…”
Section: Stilbene Biosynthesismentioning
confidence: 99%
“…To enhance its stability within the cell, resveratrol is protected from oxidation and enzymatic degradation by being glycosylated (Chong et al, 2009;Krasnow and Murphy, 2004;Hall & De Luca, 2007). An O-methyltransferase gene (romt) has been identified in grapevine, transforming resveratrol to its dimethylated derivative (Schmidlin et al, 2008) and peroxidases can oxidise resveratrol to yield the resveratrol dimer ε-viniferin (Ros-Barcelo et al, 2003). Although cis-isomers of stilbenes have been identified in grapevine, no stilbene isomerise has yet been detected in the plant.…”
Section: Stilbene Production In Plantsmentioning
confidence: 99%